The Priority of Sidomulyo Village Development Strategy as A Tourism Village for Sustainable Agriculture Batu City - Gunawan Prayitno; Widya Rizka Augusty; Wawargita Permata Wijayanti; Dian Dinanti; Aris Subagiyo; Dimas Wisnu Adrianto (Jurnal Penelitian Pertanian Terapan, 2023)
Tourism Village is currently being developed by the Batu City Government. The policy was adopted in the strategic plan of the Batu City Tourism Office in the field of tourism product development by increasing the number of tourism villages that have adequate infrastructure. However, the tourism potential of Sidomulyo Village has not been able to attract tourists to enjoy the village. The problem of Sidomulyo Tourism Village encourages the need for planning that pays attention to all aspects of the tourism village. Therefore, the study was conducted to formulate strategic priorities as a tourism village in Batu City. The sample used in this study are expert respondents. The Analytical Hierarchy Process (AHP) is used to assess the priority of development strategies. Research shows that development elements prioritized in the development of Sidomulyo Tourism Village are human resource elements with alternative priority to make community groups independent and able to build strong work teams.